Characterization of the nanoDot OSLD dosimeter in CT. Issue 4 (20th March 2015) - Scarboro, Sarah B.; Cody, Dianna; Alvarez, Paola; Followill, David; Court, Laurence; Stingo, Francesco C.; Zhang, Di; McNitt‐Gray, Michael; Kry, Stephen F.
Abstract : Purpose: The extensive use of computed tomography (CT) in diagnostic procedures is accompanied by a growing need for more accurate and patient‐specific dosimetry techniques. Optically stimulated luminescent dosimeters (OSLDs) offer a potential solution for patient‐specific CT point‐based surface dosimetry by measuring air kerma. The purpose of this work was to characterize the OSLD nanoDot for CT dosimetry, quantifying necessary correction factors, and evaluating the uncertainty of these factors. Methods: A characterization of the Landauer OSL nanoDot (Landauer, Inc., Greenwood, IL) was conducted using both measurements and theoretical approaches in a CT environment. The effects of signal depletion, signal fading, dose linearity, and angular dependence were characterized through direct measurement for CT energies (80–140 kV) and delivered doses ranging from ∼5 to >1000 mGy. Energy dependence as a function of scan parameters was evaluated using two independent approaches: direct measurement and a theoretical approach based on Burlin cavity theory and Monte Carlo simulated spectra. This beam‐quality dependence was evaluated for a range of CT scanning parameters. Results: Correction factors for the dosimeter response in terms of signal fading, dose linearity, and angular dependence were found to be small for most measurement conditions (<3%). The relative uncertainty was determined for each factor and reported at the two‐sigma level. Differences in irradiation geometry (rotational versus static) resulted in a difference in dosimeter signal of 3% on average. Beam quality varied with scan parameters and necessitated the largest correction factor, ranging from 0.80 to 1.15 relative to a calibration performed in air using a 120 kV beam. Good agreement was found between the theoretical and measurement approaches. Conclusions: Correction factors for the measurement of air kerma were generally small for CT dosimetry, although angular effects, and particularly effects due to changes in beam quality, could be more substantial. In particular, it would likely be necessary to account for variations in CT scan parameters and measurement location when performing CT dosimetry using OSLD.